Acute pulmonary edema caused by takotsubo cardiomyopathy in a pregnant woman undergoing transvaginal cervical cerclage: A case report. Issue 1 (January 2017) - Lee, Jae-Young; Kwon, Hyun-Jung; Park, Sang-Wook; Lee, Yu-Mi
Abstract: Background: The physiological changes associated with pregnancy may predispose pregnant women to pulmonary edema. Other known causes of pulmonary edema during pregnancy include tocolytic drugs, preeclampsia, eclampsia, and peripartum cardiomyopathy. Methods: We describe a rare case of pulmonary edema caused by takotsubo cardiomyopathy in a pregnant woman at 14 weeks of gestation who was undergoing emergency transvaginal cervical cerclage. Results: Intraoperative chest radiography revealed severe pulmonary edema and echocardiography indicated moderate left ventricular dysfunction with akinesia of the mid to apical left ventricular wall segment, which is reflective of takotsubo cardiomyopathy. Conclusion: With early detection and appropriate management, the patient was stabilized in a relatively short period of time. Based on her clinical signs and symptoms, we suspect that the pulmonary edema was caused by takotsubo cardiomyopathy.